Sex‐Specific Effects of Social Environment on Behaviour and Their Correlations in Drosophila melanogaster - Erin L. Macartney; Samantha Burke; Patrice Pottier; Zina Hamoudi; Chloe Hart; Radiah Ahmed; Yong Qi Lin; G. Gregory Neely; Szymon M. Drobniak; Shinichi Nakagawa (Ecology and Evolution)
ABSTRACT Environmental and individual experiences can result in immediate and persistent changes in behaviour. Often, such effects are also sex‐dependent. Intraspecific interactions can be one of the most important environments an individual faces. Such social interactions are expected to affect a suite of behavioural traits and their correlations. Here, we used Drosophila melanogaster and high‐throughput automated behavioural phenotyping to determine how social environment (group mixed sex, group single sex, and social isolation) and sex interact to affect basic behaviours (exploration, movement within a y‐maze, and habituation to a startle) that likely underlie more complex behaviours such as mate searching and foraging. We show that such behaviours and some behavioural correlations are indeed context‐ and sex‐dependent. Males tended to show greater exploration, while females were more likely to show a habituation response to startle. Males and females from the mixed sex and isolated treatments showed opposite exploratory behaviour in the Y‐maze, and social treatment interacted with sex to affect the rate of habituation to a startle. Females also tended to have slightly stronger trait correlations compared to males. These results show that social environment and sex can play a significant role in shaping behaviour in Drosophila melanogaster. Our study provides insights into how the type of social stimulation and sex can interact to affect behaviours that are important in forming critical behaviours related to foraging and mate searching.